2012
DOI: 10.1016/j.jcrc.2011.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Emotional consequences of intensive care unit delirium and delusional memories after intensive care unit admission: A systematic review

Abstract: Based on current literature, no relationship could be shown for delirium and emotional outcome. Regarding delusional memories and adverse emotional outcome, results were in contradiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…17 The presence of delusional memories may suggest ICU delirium however, a systematic review found no relationship between delirium and PTSD. 18 …”
Section: Introductionmentioning
confidence: 99%
“…17 The presence of delusional memories may suggest ICU delirium however, a systematic review found no relationship between delirium and PTSD. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, benzodiazepines can have a prolonged half-life in critically ill patients. 23 Although the findings from a recent meta-analysis 24 raise questions about the relationship between these medications and delirium, the Society of Critical Care Medicine 2013 guidelines, 25 based on available evidence, state that "sedation strategies using nonbenzodiazepine sedatives may be preferred over sedation with benzodiazepines. "…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis 24 of 34 studies indicated that although delirium alone is not correlated with PTSD, whether or not memories of delirious episodes are contributory is unclear. As Weinert and Sprenkle 20 suggest, the character of the ICU experience may have a greater influence on psychological outcomes than the level of sedation does.…”
Section: Gaps In Researchmentioning
confidence: 99%
“…9 The lowest dose of sedation agent should be administered to achieve patient comfort, and when possible, benzodiazepine agents should be limited or avoided. [1][2][3][4][5]9 Frequently assessing the patient's readiness to wean from mechanical ventilation is another intervention that may be used to reduce the risk of PICS. Performing daily spontaneous awakening trials coupled with spontaneous breathing trials is important to allow a reduction in sedation agents, perform a neurologic assessment, and evaluate the patient's readiness to extubate.…”
Section: Icu Survivorship and Beyondmentioning
confidence: 99%
“…Cognitive and psychological stressors frequently occur arising from sleep deprivation, sedation, anxiety, fear, delusional memories, and delirium. 3 A rising body of evidence reports cognitive and psychological consequences for ICU survivors that alter the patient's reported quality of life. Recent studies estimate 25% to 75% of ICU survivors report challenges with depressive symptoms, anxiety, cognitive impairment, and/or posttraumatic stress disorder.…”
mentioning
confidence: 99%